Managerial Tools of Academic Knowledge Formation Process - Zulfiya F. Yusupova; Muslima M. Shakurova; Nikolay Y. Saygushev; Olga A. Vedeneeva; Svetlana G. Kashina (International Review of Management and Marketing, 2016)
The relevance of the study is conditioned by the requirement of modern society to improve the quality of education. Knowledge is a core component in the educational content, along with the skills and competencies. The purpose of the paper is to determine the managerial tools of formation process of academic knowledge. The leading approach to the study is the process approach, allowing to characterize the quality of the academic knowledge (consistency, continuity, generality, efficiency, integrity) and to consider the management of academic knowledge's formation as a set of interrelated and interactive educational activities, ensuring the efficiency of their assimilation, understanding and application. The paper reveals the functions of academic knowledge (ontological, indicative, motivational); clarifies and scientifically proves managerial tools of the formation process of academic knowledge (case study, informational and event-based learning environment, research method, cognitive tools, unifying language and symbolic systems, visual AIDS, technical training). The paper submissions can be useful for managers and teachers of educational institutions; employees of the centers for advanced training and retraining of personnel in the selection and structuring of the content for the training of scientific and pedagogical staff.